Hepatic vein flow pattern in children: assesment with Doppler sonography - AHMETOGLU, Ali; KOSUCU, Polat; ARIKAN, Elif; DINC, Hasan; GÜMELE, Halit Resit (European journal of radiology, 2005)
Background: Aim of this study is to establish normal hepatic vein flow pattern and effect of age, sex, activity and feeding status on the hepatic flow pattern in normal Turkish children less than 15 years of ages and also to compare our values with the previously reported studies. Method: Hepatic vein flow patterns were evaluated in 150 children (83 male, 67 female) without any cardiac, pulmonary and liver disease by using Doppler sonography. Blood flow patterns were compared with age, sex, activity, and feeding status of the children. Results: Only 44% of the children had triphasic flow pattern in all hepatic veins. Monophasic flow pattern was the most common flow pattern in children less then 1 year of age. Triphasic flow pattern increase after 1 year of age. Although most of the children older than 1 year of age had triphasic flow pattern, there is some variation in the flow patterns of the hepatic veins in the same subject. Triphasic hepatic flow pattern is most commonly seen in the left hepatic vein and least commonly seen in the right hepatic vein. There was no significant difference between male and girl, children who were agitated or calm and fasting or not fasting in respect to triphasic flow pattern. Conclusion: Liver stiffening is not only the reason for abnormal hepatic flow pattern and some other physiologic factors may also lead to mono and/or diphasic flow pattern in the children. Absence of triphasic flow pattern must not be accepted as a liver pathology in children especially younger than 1 year of age.